Improving Students' Vocabulary In Descriptive Text Through Words Mapping Technique at SMP Negeri 2 Tompaso - Wuon, Jilia; Pelenkahu, Noldy; Kumayas, Tirza A. (Program Studi Pendidikan Bahasa Inggris, 2025)
The purpose of the study is to determine whether the word mapping technique can improve students’ vocabulary. The research involved 20 students from class VIII at SMP N 2 Tompaso. This study is a quantitative research using pre-experimental design with pre-test and post-test design. Data were collected using multiple-choice test, each consisting of 15 items. The result reveals a significant improvement in student performance between the pre-test and the post-test. The average score increased from 47,7 in the pre-test to 81,5 in the post-test. This suggests that word mapping technique effectively improves students’ vocabulary at SMP Negeri 2 Tompaso. Furthermore, students reported that word mapping helped them improve their vocabulary and write descriptive text more effectively. This research recommends using the word mapping technique as an alternative teaching strategy, especially in teaching vocabulary for descriptive texts, to improve students’ vocabulary in school.